Oral health in patients with cleft lip and palate: a systematic literature review and meta-analysis of periodontal and dental disease and oral microbiota (part 1) - A. Pardo; V. Vanti; F. Lonardi; A. Signoriello; G. Lobbia; G. Lombardo; L. Trevisiol; A. D’Agostino (BMC Oral Health)
Abstract Introduction Orofacial cleft impacts jawbone and dental development and function, often with consequences for oral health. The first in this two-part systematic review of the literature on oral health in persons with cleft lip and/or palate focuses on periodontal parameters and composition of oral bacterial flora, while the second analyzes data on dental caries. Materials and Methods Four databases (PubMed, Cochrane, Scopus, Web of Science) were searched for studies that compared periodontal parameters, caries index, and microbiota composition between persons with cleft lip and/or palate and healthy controls. The Newcastle–Ottawa scale and the Joanna Briggs Institute checklist were applied to evaluate study quality. Results A total of 24 studies underwent systematic review, 18 of which entered meta-analysis. Twenty studies included a control group, while four included only persons with orofacial cleft. The first part (18 studies) compared periodontal parameters and oral microbiota. Conclusions Meta-analysis of periodontal parameters (plaque index, gingival index, bleeding index, probing pocket depth, clinical attachment level) revealed an association between orofacial cleft and greater risk for poor oral health and periodontal disease. Good oral health relies on correct home oral hygiene and regular visits to the dentist starting at an early age.